2019
DOI: 10.3390/ma13010021
|View full text |Cite
|
Sign up to set email alerts
|

Li+ Insertion in Nanostructured TiO2 for Energy Storage

Abstract: Nanostructured materials possess unique physical-chemical characteristics and have attracted much attention, among others, in the field of energy conversion and storage devices, for the possibility to exploit both their bulk and surface properties, enabling enhanced electron and ion transport, fast diffusion of electrolytes, and consequently high efficiency in the electrochemical processes. In particular, titanium dioxide received great attention, both in the form of amorphous or crystalline material for these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…[69] Mara et al also demonstrated that amorphous TiO 2 formed at low temperature and anatase TiO 2 formed at high temperature, suggesting that the oxidation temperature needs to be tuned to obtain ideal amorphous structured materials. [70] Moreover, metal can be oxidized to metal oxide according to the reaction formula: 2xM + yO 2 → 2 M x O y . However, the reaction conditions are more stringent and difficult relative to the decomposition of metal hydroxide due to the superior stability of metal elements.…”
Section: Thermal Treatmentmentioning
confidence: 99%
“…[69] Mara et al also demonstrated that amorphous TiO 2 formed at low temperature and anatase TiO 2 formed at high temperature, suggesting that the oxidation temperature needs to be tuned to obtain ideal amorphous structured materials. [70] Moreover, metal can be oxidized to metal oxide according to the reaction formula: 2xM + yO 2 → 2 M x O y . However, the reaction conditions are more stringent and difficult relative to the decomposition of metal hydroxide due to the superior stability of metal elements.…”
Section: Thermal Treatmentmentioning
confidence: 99%
“…Serrapede et al [30] have compared and quantified the charging mechanisms of defective TiO 2 with respect to stoichiometric anatase. The porous TiO 2 samples have been synthesized by simple thermal oxidation of titanium foil in a 111 volume hydrogen peroxide solution (30% (w/w) in H 2 O) at low temperature.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Titanium dioxide (TiO2) is one of the most extensively investigated materials for various applications like photo-catalysis, photo degradation, energy storage, photovoltaic devices and optoelectronic devices [1,2]. In the last decade, one-dimensional (1D) TiO2 nanostructures have been significantly studied because of their ability to enhance the light absorption due to scattering of lights inside the nanostructure, which facilitates the photocatalytic reactions and by providing the direct pathway for charge carrier [3].…”
Section: Introductionmentioning
confidence: 99%